Beneath the surface: unveiling the gut–brain axis in anorexia and depression - Fatima Shahid; Zain Afridi; Muhammad Ali; Muhammad Nabeel Saddique; Javed Iqbal; Anurag Jha (Eating and Weight Disorders)
Abstract Anorexia nervosa (AN) and depression are complex conditions with high comorbidity, impacting mental and physical health. Recent research suggests gut microbiota plays a significant role in their development and progression. This correspondence highlights the critical gaps in understanding the gut–brain axis in AN and depression, emphasizing the need for comprehensive research. We discuss recent findings, including altered gut microbiota profiles and inflammatory factors, and identify key areas for future investigation. These include large-scale, multi-center studies to quantify microbiota profiles, mechanistic understanding of gut microbiota alterations, and diagnostic and therapeutic advances using microbiota as biomarkers. Addressing these gaps is crucial for developing effective treatment strategies and improving patient outcomes. By exploring the underlying mechanisms, validating biomarkers, and developing targeted therapies, we can enhance diagnostic accuracy, improve treatment outcomes, and better support patients with AN and depression. This research has the potential to transform the management of these conditions and improve quality of life for those affected. Level of evidence Low level of evidence as it is a personal opinion.